Studi Instalasi Listrik Gedung Sekolah Dasar Negeri 002 Bontang Utara - Qomaruddin; Arbain; Aidil Akbar Saddam Indarmawan (PT. PENERBIT TIGA MUTIARA, 2026)
Electrical installations in school buildings play a vital role in ensuring safety, comfort, and effective learning environments and therefore must comply with the General Requirements for Electrical Installations (PUIL). This study aims to analyze the electrical installation condition of SDN 002 Bontang Utara through the evaluation of lighting systems, power requirements, conductors, protection systems, and air conditioning based on PUIL 2011 standards and DIALux simulation. The study employed a field research method with a quantitative descriptive approach through observation, technical measurements, documentation, and lighting simulation analysis. The findings indicate that the school’s electrical installation still exhibits several discrepancies with actual technical requirements, particularly regarding the number and capacity of lamps, air conditioner capacity, and electrical power demand. DIALux simulation revealed that several rooms have not yet met the required lighting standards, while power analysis demonstrated that the actual demand of 25,794 VA exceeds the installed capacity of 22,188.8 VA, thereby necessitating adjustments to the protection and conductor systems to enhance installation safety and efficiency. The study concludes that the electrical installation of SDN 002 Bontang Utara requires improvements in lighting, cooling systems, power capacity, and electrical protection. The novelty of this research lies in its integrated evaluation of elementary school electrical installations through field analysis, PUIL 2011 technical calculations, and DIALux simulations across rooms with diverse functions, thereby producing more comprehensive and applicable recommendations.